The Effect of Job Satisfaction and Job Loyalty on Employee Performance: A Narrative Literature Review - Adelia Hartika; Mutiara Fitridiani; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2023)
The purpose of writing this article is a narrative literature review of 3 (three) articles that discuss the effect of job satisfaction and job loyalty on employee performance with the aim of identifying and summarizing previously published articles without any criticism of the articles reviewed. In achieving the goals or objectives to be achieved, companies need to pay attention to one of them is producing data that is inconsistent or sometimes does not reach the production target, this is due, among other things, two indications of weak job satisfaction and job loyalty which have an impact on employee performance that is less noticed. The review results show that the effect of job satisfaction and job loyalty of the 3 articles shows a positive and significant effect on employee performance.